2014
DOI: 10.1017/jgc.2014.12
|View full text |Cite
|
Sign up to set email alerts
|

A Combined Intervention Targeting both Teachers’ and Students’ Social-Emotional Skills: Preliminary Evaluation of Students’ Outcomes

Abstract: The literature indicates increasing evidence showing the benefits of classroombased, universal preventive interventions for mental health and the link between social and emotional learning and academic performance. The FRIENDS program has been extensively tested and has showed promising results not only for preventing childhood anxiety, but also for improving students' self-concept, social skills and coping skills. However, when it comes to communities in disadvantage, the results are mixed, with some studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Though classroom observation is a time-consuming method it has the obvious advantage compared to self-rating-scales, that the possible`blind-spots´in the teachers' self-awareness is addressed by looking at their actual practice. Interestingly only two of the studies reviewed addresses students' perceptions of changes following implementation (Doikou-Avlidou, And, and Dadatsi 2013;Lizuka et al 2014). Students perspectives on e.g.…”
Section: Theme 5: Methodology In the Reviewed Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Though classroom observation is a time-consuming method it has the obvious advantage compared to self-rating-scales, that the possible`blind-spots´in the teachers' self-awareness is addressed by looking at their actual practice. Interestingly only two of the studies reviewed addresses students' perceptions of changes following implementation (Doikou-Avlidou, And, and Dadatsi 2013;Lizuka et al 2014). Students perspectives on e.g.…”
Section: Theme 5: Methodology In the Reviewed Researchmentioning
confidence: 99%
“…Durlak (2016, 339-40) refers to`The child development project´, Responsive Classroom, PATHS and SEAL. There are also specific programs just referred to by one author like SET (social and emotional training) in Sweden (Kimber, Skoog, and Sandelic 2013), the Second Step program in Norway (Larsen and Samdal 2011) and the FRIENDS program in Australia (Lizuka et al 2014).…”
Section: Theme 1: Sel Intercultural Competency and Intercultural Senmentioning
confidence: 99%
“…Indeed, several primary prevention programs were developed for teaching self-control, social competence, positive peer relations and interpersonal problem solving (Collaborative for academic, social and emotional learning, 2014). However, these programs focus on teaching these skills to students and do not provide explicit instructions to promote social and emotional literacy among teachers (Iizuka, Barrett, Gillies, Cook, & Marinovic, 2014). Rather, they assume that the teacher is prepared to act as an effective emotional coach and role model (Jennings & Greenberg, 2009).…”
Section: Research On Teacher Training On Social and Emotional Learningmentioning
confidence: 99%
“…The triadic model of resilience (Garmezy, ) has been used to study resilience in multiple settings (Iizuka, Barrett, Gillies, Cook, & Miller, ; Macedo et al, ), as it emphasises how an individual can impact on their environment as well as be shaped by the interaction. The triadic model describes the salient protective and risk factors affecting the process of resilience on three levels – individual (e.g., traits such as intelligence or social skilfulness), family (e.g., parental warmth or maltreatment) and community (e.g., neighbourhoods and social supports) – work together to shape development and growth.…”
mentioning
confidence: 99%
“…Research evidence has identified many advantages to universal prevention programmes that can reach a broad range of the population with varying levels of psychopathology, including individuals not at risk, “at risk,” or with sub‐clinical and clinical symptoms by enhancing protective factors and reducing risk factors (Barrett, Farrell, Ollendick, & Dadds, ). The potential advantages include reducing stigmatisation by addressing individuals with differing levels of psychopathology, improving peer support, promoting social and emotional wellbeing, self‐esteem and healthy development (Iizuka et al, ). As universities have access to resources, infrastructure and the adolescent and adult population for longer periods of time, they have the potential to offer an optimal setting for universal prevention‐focussed interventions (Stallman, ).…”
mentioning
confidence: 99%